LEGALITAS PEMUSNAHAN BARANG BUKTI NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2004 TENTANG KEJAKSAAN REPUBLIK INDONESIA - Heryanto, Eko (Lex LATA, 2024)
Narcotics are basically good for development needs in the fields of health, science and technology. As a public prosecutor, the prosecutor not only makes charges against the defendant but also against the items that are evidence, where the demands require that the evidence be destroyed, confiscated for the benefit of the state or returned to its rightful owner. This research is a type of normative research. The results of this research show that the Legality of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia regarding the Destruction of Narcotics Evidence does not regulate the destruction of Narcotics Evidence. The destruction of Narcotics Evidence is regulated in Law Number 35 of 2009 concerning Narcotics, Government Regulation Number 40 of 2013 concerning Implementation of Law Number 35 of 2009 concerning Narcotics, as well as Regulation of the Head of the National Narcotics Agency Number 7 of 2010 concerning Technical Guidelines for Handling and Safe destruction of confiscated narcotics, narcotics precursors and other chemicals.